Acceptability and Fiber Content of Bolu Kukus with Addition Purple Uwi Flour ( Diocorea Alata ) as Snacks High Fiber - Citra Dewi Ayu Lestari; Hikmawati Mas'ud; Suriani Rauf (Media Gizi Pangan, 2019)
Progress of times which fast have been have an impact on unhealthy diet. One of habits that often happen is consume snacks that high fat and low fiber.This usually happen in urban society, they prefer to consume fast foods. Purple uwi flour can made as snacks that high fiber. Food product that can made as healthy snacks that high fiber, is Bolu kukus eith addition purple uwi flour.This research aim know the acceptability and analysis fiber content of bolu kukus addition purple uwi flour (Dioscorea alata ) as snacks high fiber. Design of research is experimental with design one shot group design. The acceptability assased  based on the hedonic test with 30 panelists.Results of best acceptability analyzed fiber content, testing in laboratory use method fiber food . Then presented in form table and narration.The result of organoleptic test based aspect of color, aroma texture, and taste, the most highest liked by panelists is concentration of 20%.The value of fiber contant that has been analyzed 24,04%, so that it could consumed as snacks high fiber. According to Recommended Dietary Allowance (RDA) intake fiber children or adults is 15-30 grams/day with consider portions every meal. Suggested manufacture of  bolu kukus with addition purple uwi flour should use concentration 20%, because from aspect color, aroma, texture, and flavor is the most good and liked. Analysis macro and micro nutrition anddo test saving power on Bolu kukus.